Tuberkulosis Paru Terkonfirmasi Bakteriologis dengan Komplikasi Pneumotoraks - Dwi Rizki Fadhilah; Irvan Medison; Dewi Wahyu Fitrina; Dessy Mizarti (Jurnal Syntax Admiration, 2024)
This study aims to identify epidemiological characteristics, analyze risk factors, evaluate clinical management, and assess long-term outcomes in patients with bacteriologically confirmed pulmonary tuberculosis and pneumothorax complications. Simple studies can be performed to evaluate the effectiveness of bacteriological confirmed pulmonary tuberculosis management approaches with pneumothorax complications. This study will involve retrospective analysis of medical data from patients who have been diagnosed with bacteriological confirmed pulmonary tuberculosis and have pneumothorax complications in a health facility. The data to be collected includes information about patient characteristics, such as age, sex, smoking history, BCG immunization status, and history of comorbidities such as HIV/AIDS or diabetes. The results of the study above that the patient had pulmonary tuberculosis infection that had been confirmed through bacteriological tests, and also experienced complications in the form of pneumothorax, which is a buildup of air in the pleural cavity that results in pressure on the lungs. This condition requires careful medical attention and proper management to effectively address both issues and optimize the patient's recovery.